2022
DOI: 10.34257/gjmbrdvol21is2pg17
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Accounting Disclosure and Financial Performance of Listed Multinational Firms in Nigeria

Abstract: The study investigated environmental accounting disclosure and financial performance of listed multinational companies in Nigeria. This study was conducted by firstly assessing the level of compliance, and then exploring the effect of environmental disclosure on financial performance with a focus on multinational companies in the face of continued environmental abuse witnessed in the Nigerian business space owing to the non-availability of sustainability reporting legal framework. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…However, FIRS had a negative but insignificant effect on ROA. These findings are consistent with previous studies such as Tomomewo et al (2022), Igbekoyi et al (2021), and Nejla and Haithom (2022), which also found no significant relationship between ES reporting and FP in DMBs and firms. On the other hand, these findings contradict the conclusions of other studies conducted by Olakunle (2015), ABM, Ruzlin and Jeaneth (2021), Zamil and Hassan (2019) and Atanda et al (2021), which suggested that ES practices have a significant impact, both positive and negative, on the FP of SMEs, financial institutions, banks, and firms.…”
Section: Hypothesis Four H04supporting
confidence: 93%
See 1 more Smart Citation
“…However, FIRS had a negative but insignificant effect on ROA. These findings are consistent with previous studies such as Tomomewo et al (2022), Igbekoyi et al (2021), and Nejla and Haithom (2022), which also found no significant relationship between ES reporting and FP in DMBs and firms. On the other hand, these findings contradict the conclusions of other studies conducted by Olakunle (2015), ABM, Ruzlin and Jeaneth (2021), Zamil and Hassan (2019) and Atanda et al (2021), which suggested that ES practices have a significant impact, both positive and negative, on the FP of SMEs, financial institutions, banks, and firms.…”
Section: Hypothesis Four H04supporting
confidence: 93%
“…On the other hand, these findings contradict the conclusions of other studies conducted by Olakunle (2015), ABM, Ruzlin and Jeaneth (2021), Zamil and Hassan (2019) and Atanda et al (2021), which suggested that ES practices have a significant impact, both positive and negative, on the FP of SMEs, financial institutions, banks, and firms. In this study, it is argued that ES is more of an ethical practice rather than a resourcebased practice for DMBs, and therefore does not necessarily affect their FP (Igbekoyi et al, 2021). Overall, the findings of this study are consistent with stakeholder theory, legitimacy theory, and agency theory, supporting a positive relationship between ES practices and the FP of the quoted DMBs in Nigeria though it is insignificant.…”
Section: Hypothesis Four H04supporting
confidence: 74%
“…IFRSs implementation is vital to a sound financial regulatory framework and corporate governance (Okoye & Ofoegbu, 2006). Financial reporting is a crucial element necessary for corporate governance to function effectively (Igbekoyi & Agbaje, 2018). IFRSs implementation is geared at improving transparency and disclosure of items in the financial statements.…”
Section: Ifrss and Corporate Governancementioning
confidence: 99%
“…Organizations today are becoming increasingly aware of environmental concerns, owing to which their leaders are trying to incorporate environmental factors into their strategic planning and decision-making (Elkington, 1997). Some studies have shown that being aware of environmental issues can mitigate information asymmetry and improve the quality of sustainability reports, which leads to a good brand image (Igbekoyi and Olaleye, 2020). The literature also highlights that concern for the environment could be linked to B2B sustainability positioning (Kapitan et al, 2019).…”
Section: Hypothesis Development and Conceptual Frameworkmentioning
confidence: 99%